Optimization of CO2 Supply for the Intensive Cultivation of Chlorella sorokiniana IPPAS C-1 in the Laboratory and Pilot-Scale Flat-Panel Photobioreactors - David A. Gabrielyan; Boris V. Gabel; Maria A. Sinetova; Alexander K. Gabrielian; Alexandra G. Markelova; Natalia V. Shcherbakova; Dmitry A. Los (Life, 2022)
Microalgae are increasingly being used for capturing carbon dioxide and converting it into valuable metabolites and biologically active compounds on an industrial scale. The efficient production of microalgae biomass requires the optimization of resources, including CO2. Here, we estimated the productivity of Chlorella sorokiniana IPPAS C-1 depending on CO2 concentrations and the ventilation coefficient of the gas-air mixture (GAM) in flat-panel photobioreactors (FP-PBRs) at laboratory (5 L) and pilot (18 L) scales. For the laboratory scale, the PBRs operated at 900 µmol quanta m−2 s−1 and 35.5 ± 0.5 °C; the optimal CO2 flow rate was estimated at 3 mL CO2 per 1 L of suspension per minute, which corresponds to 1.5% CO2 in the GAM and an aeration rate of 0.2 vvm. These parameters, being scaled up within the pilot PBRs, resulted in a high specific growth rate (µ ≈ 0.1 h−1) and high specific productivity (Psp ≈ 1 g dw L−1 d−1). The principles of increasing the efficiency of the intensive cultivation of C. sorokiniana IPPAS C-1 are discussed. These principles are relevant for the development of technological regimes for the industrial production of Chlorella in flat-panel PBRs of various sizes.